Estudo do perfil metabólico no exercício físico e no envelhecimento: uma abordagem metabolômica integrada à modulação autonômica cardíaca - Signini, Étore De Favari (Universidade Federal de São Carlos, 2023)
Physical exercise and aging are natural stressors with antagonistic outcomes in the human body. Such outcomes are phenotypically reflected in metabolism, which can be studied through metabolomics. The latter allows the study of oxylipins (lipid metabolites that have important relationships with physical exercise outcomes) and the comprehensive integration of metabolism with other components related to systemic integrity, such as cardiac autonomic modulation (CAM) and cardiorespiratory fitness (CRF), helping to understand the integrated outcomes provided by aging. A better understanding of these stressors through the use of metabolomics and integrative analysis can help in the development of more efficient health promotion strategies for the general population. Thus, Study 1 was a systematic review of the literature and sought to investigate the responses of oxylipins related to the short- and long-term effects of physical exercise through their enzymatic pathways and to provide information about the potential physiological effects. After the search and selection, only 9 studies out of 1,749 documents were included due to the inclusion and exclusion criteria. Of these, seven emphasized short-term effects, while two evaluated long-term effects on the oxylipin profile. In conclusion, several oxylipins with biomodulatory functions mainly related to inflammation, cardiovascular function, and tissue adaptation and regeneration, were mobilized especially as a consequence of the short-term effects of physical exercise, under the influence of the intensity and duration of physical exercise. The long-term effects of physical exercise on the levels of different oxylipins were minimal and related to different functions. Study 2 investigated, in an integrated manner, the timecourse of variables of the human metabolome and variables related to CAM and CRF in aging, in different age groups considering apparently healthy individuals. The individuals aged 20 to 70 years were divided into five age groups (20-29, 30-39, 40-49, 50-59, and 60-70 years) and submitted to blood collection, cardiac autonomic evaluation and cardiopulmonary exercise test, for metabolomics, CAM and CRF analysis, respectively. Tukey's post hoc and effect size with the confidence interval were used for all metabolites and significant variables in the one-way ANOVA model, with p<0.01, and principal component analysis (PCA) on the significant variables for the integrated study. Significant changes were observed in the 60-70 age group, where CRF, BCAAs (valine, leucine and isoleucine), 3-hydroxyisobutyrate and CAM were found to be significantly reduced, while hippuric acid was significantly elevated compared to younger groups (especially for the 20-29 and 30-39 age groups). Hippuric acid, CAM and CRF variables, and BCAAs were the main responsible for age group distinction as highlighted in the PCA. In conclusion, the results suggest significant changes in metabolism, CAM, and CRF, after the age of sixty as a consequence of the aging process, however, with some changes in the metabolic profile that may be favorable in mitigating the deleterious effects of aging. This thesis showed the complexity of the interrelation between metabolism and some systems of the body in an integrated manner in the context of natural stressors of the body such as physical exercise and aging. Such information is important considering the necessity for a less fragmented understanding of human physiology.
Study of the metabolic profile in physical exercise and aging: an integrated metabolomics approach to cardiac autonomic modulation
Keywords: Envelhecimento; Aptidão cardiorrespiratória; Metabolômica; Exercício físico; Frequência cardíaca; Aging; Cardiorespiratory fitness; Metabolomics; Physical exercise; Heart rate; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL